Analysis of Structure and Efficiency of Fresh Tomato Retail Marketing in Benue State Nigeria - Ocholi, A. Agada S. G. (European Journal of Applied Sciences, 2021)
Efficient tomato marketing depends on how the market is organized in-terms of interrelationship between buyers and sellers. The study investigated the structure and efficiency of fresh tomato retail marketing in the study area. Purposive, Multistage and Simple random sampling method was employed to select 50 fresh tomato retailers in the study area. Primary data were collected using structured questionnaire administered on respondents. Data collected were analyzed using Descriptive Statistics, Marketing Efficiency, Gini Coefficientand Gross Margin. The study revealed that the majority (56%) of the respondent were male while (44%) were female. 46% were married with a mean age of 38 years and a mean income of N50404. The result further showed marketing efficiency of 19.30 indicating that the product was efficient in the study area. The Gini Coefficient was 0.63 which implies that there was competition among tomato retailers in the study area. Despite the intrinsic characteristics of fresh tomato fruits, its sale was profitable judging by the mean Gross Margin of 10, 654.8. Transportation and storage facilities constituted the greatest challenge faced by tomato retailers in the study area. Based on the finding of the studies it was recommended that the retailers should form cooperatives to promote bulk purchase which will in turn reduce transportation charges as well as enable them to achieve the benefits from economies of scale.